Reimagining Healthcare Pathways: Addressing Workforce Mobility In Saudi Arabia And Global Integration (The Review of Diabetic Studies, 2024)
Saudi Arabia is undergoing a remarkable transformation in its healthcare sector, driven by Vision 2030's ambitious goals. One critical aspect of this shift is addressing workforce mobility—a challenge that spans local retention, international integration, and global competitiveness. With healthcare professionals increasingly seeking opportunities across borders, Saudi Arabia faces the dual challenge of retaining its talent while embracing international collaboration. This paper delves into the complexities of workforce mobility, exploring strategies to enhance talent retention, streamline international recruitment, and foster global partnerships. By aligning local priorities with international standards, Saudi Arabia has the potential to shape a resilient and globally integrated healthcare workforce.